History of developments in sport and exercise physiology: A. V. Hill, maximal oxygen uptake, and oxygen debt - Hale, T. (Journal of Sports Sciences, 2008)
This paper provides a thumb-nail sketch of some of the key issues that have been instrumental in the development of the scientific study of exercise, and more particularly sports, physiology. Those who have had the pleasure of reading the American Physiological Society's publication Exercise Physiology in its "People and Ideas" series, will know the breadth and depth of the extant material in this field. In an attempt at some form of coherence, the present paper focuses on the concepts of maximal oxygen uptake and oxygen debt introduced by the British physiologist Archibald Vivian Hill in 1922. The Introduction provides a contextual framework for the paper, and is followed by a description of the work undertaken by Hill and his colleagues in the development of these concepts over a three-year period. Credit is given to scientists from the eighteenth century onwards who provided the scientific foundations that led to the measurement of oxygen uptake, and those who went on to elaborate the physiological mechanisms of aerobic and anaerobic metabolism. The problems in what constitutes a plateau and how to get it are discussed, along with attempts to predict maximal oxygen uptake from sub-maximal - or even no - exercise. The debate surrounding the limiting factor in the oxygen uptake chain started by Hill is brought up to date rather than resolved. The ecological validity of applied sports physiology is explored in terms of sport-specific ergometry and test protocols. Finally, Hill's interest in the production and removal of lactic acid re-emerges in the recent attempts to establish the threshold at which accumulation of lactic acid in the blood leads to cessation of exercise, and also the means of validly measuring an individual's anaerobic power and capacity. Wherever possible and appropriate, counter-arguments are introduced to demonstrate the transient and uncertain nature of what is often regarded as true knowledge.